ANALISIS EKONOMI PENGEMBANGAN KAWASAN BUNTAGO - djawardi, djawardi (Badan Pengkajian dan Penerapan Teknologi, 2009)
Buntago Zone consists of Buntok, Tanjung and Tanah Grogot is the area each other adjacent and border on the Province Central of Kalimantan, South of Kalimantan and East of Kalimantan. Buntok is “Kawasan Andalan” in Barito Regency, Tanjungis one of the Local Activity Center (PKL) support zone for “Kawasan Andalan” Kandangan in Tabalong Regency, and Tanah Grogot is Capital city of Pasir Regency is Regional Activity Center (PKW) support zone for “Kawasan Andalan: Bonsamtebajam. The development plan of Buntago is expected to become acoordinating tool and also a basic preparation for inter sectoral and inter regional development programs. The usage of this plan is also to regulate interregional potencies in order to optimalize their contribution for the development of communityeconomic welfare. Buntago zone have the prospect to be developed mutual profit together with pre-eminent commodity palm coconut and rubber. The development plan of Buntago zone divided into two scenarios. Stage 1 is the scenario for themanagement of development basics (2006-2010) and stage 2 is the scenario of development growth acceleration (2011-2015). The need of investment projected for funding this development is over 25 billion IDR. The investment needed for funding in the stage 1 is amount of 7 billion IDR, and for the stage 2 is 17 billion IDR. In order to support the development of Buntago, the government is projected to give 80% of total budget needed in the stage 1 and 60% in the stage 2, while therest will be covered by private sector.